Our malady lessons in liberty and solidarity - Timothy Snyder (London Vintage Digital, 2020)
On December 29, 2019, historian Timothy Snyder fell gravely ill. Unable to stand, barely able to think, he waited for hours in an emergency room before being correctly diagnosed and rushed into surgery. Over the next few days, as he clung to life and the first light of a new year came through his window, he found himself reflecting on the fragility of health, not recognized in America as a human right but without which all rights and freedoms have no meaning.
Keywords: Medical care -- United States; Health care reform -- United States; Right to health -- United States